Piezoelectric hydrogel for promoting myocardial repair, preparation method and use thereof
Patent Information
- Application Number
- CN202611481050.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-22
- Publication Date
- 2026-10-30
AI Technical Summary
此外,受材料生物安全性、植入相容性及可注射微创递送等因素的制约,将离子压电效应由传感监测向组织修复应用延伸,特别是在心脏组织修复领域,面临新的科学与技术挑战
本发明通过阴阳离子非对称迁移动力学与微观限域结构协同设计(图1),将电中性聚丙烯酰胺微球与荷电聚硫辛酸钠基体结合,使其能够在心脏搏动机械能驱动下产生内源性离子电势,实现了无外源电源的原位、持续电刺激,以及机械能向离子电信号转化,为梗死心肌提供适配电刺激,协同抗氧抗炎化作用,高效修复心肌组织并重建电生理功能。该水凝胶兼具优异的力学稳定性、组织黏附性、自修复能力及离子压电性能(50 kPa压力下输出电压约0.45 V)。此外,本发明突破了传统导电水凝胶与压电材料难以自主产生适配性离子电刺激的瓶颈,为心肌梗死的无源原位长效治疗提供了一种可转化的新策略。
Smart Images

Figure CN122998339A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of biomedical materials technology, specifically relating to a piezoelectric hydrogel that promotes myocardial repair, its preparation method, and its uses. Background Technology
[0002] Following myocardial infarction (MI), irreversible necrosis occurs in the ischemic cardiomyocytes, leading to the gradual formation of non-contractile, non-conductive fibrotic scars at the infarct site. This disrupts cardiac electromechanical synchrony, induces ventricular remodeling, and ultimately results in heart failure. Current clinical treatments such as drug therapy, myocardial reperfusion, and polarization therapy can only slow disease progression; they cannot reverse fibrosis, reconstruct electrophysiological pathways in the infarcted area, or inhibit adverse remodeling. Therefore, simultaneously achieving structural repair and electrophysiological function reconstruction of infarcted myocardial tissue is a core clinical challenge in the treatment of myocardial infarction.
[0003] To address these clinical needs, the rapid development of biomedical materials has offered new possibilities for myocardial infarction repair. Conductive hydrogels, with their mechanical properties matching myocardial tissue and their tunable physicochemical properties, have become highly promising candidate materials in this field. Their core advantages are mainly reflected in three aspects: First, the introduction of adhesive components such as catechols and mucopolysaccharides, as well as bioactive peptides, enables close adhesion to the infarcted myocardium, ensuring precise drug delivery. Second, loading anti-inflammatory, antioxidant, and pro-angiogenic factors can construct a local microenvironment conducive to repair, synergistically achieving myocardial structural protection and functional repair. Third, their excellent conductivity allows for real-time monitoring of cardiac motion, while simultaneously compensating for electrical conduction defects in the infarcted area through a conductive network, helping to restore cardiac electrophysiological synchronicity.
[0004] However, current research has not fully resolved the fundamental problems in myocardial infarction repair. While existing conductive hydrogels can monitor cardiac pathological signals, they cannot autonomously generate electrical stimulation adapted to the myocardial microenvironment, making it difficult to efficiently reconstruct and activate the electrical conduction pathways of damaged myocardium. This key scientific issue severely restricts their clinical application value in the repair and electrophysiological function reconstruction of infarcted myocardium. To compensate for this deficiency, existing research has attempted to endow them with electrical stimulation function through external power sources or implanted batteries, but both have significant limitations. External power sources rely on specialized equipment and manual operation, which is cumbersome, and the electrical signals are easily absorbed and attenuated during their passage through tissue, resulting in limited stimulation efficacy reaching the lesion. Implanted batteries face the risk of postoperative infection, and their toxicity and invasive procedures may interfere with the myocardial healing process, making it difficult to meet long-term repair needs.
[0005] Piezoelectric materials, as a novel type of electrostimulation material capable of generating their own electrical signals, offer a feasible approach to overcoming the aforementioned bottlenecks. Existing research has demonstrated that piezoelectric materials exhibit excellent regulatory efficacy in various tissue regeneration scenarios, including wound healing, cartilage repair, and myocardial repair. The electrical stimulation they generate can modulate cell membrane potential, activate key signaling pathways such as calcium channels, PI3K-Akt, and MAPK, induce directed cell differentiation, and promote the maturation of functional cells and the orderly remodeling of tissues, providing a solution to overcome the limitations of traditional conductive hydrogels in terms of autonomous electrical stimulation capabilities.
[0006] However, directly applying traditional piezoelectric materials to myocardial repair still faces significant limitations. The electromechanical conversion of inorganic piezoelectric ceramics and organic piezoelectric polymers relies on solid-state lattice distortion or molecular chain orientation deflection to generate electronic conduction currents, requiring strong mechanical stimulation or external ultrasound assistance, which is incompatible with the mild physiological pulsation environment of the heart. More importantly, the electronic electrical signals they generate are fundamentally different from the ionic physiological electrical signals in the body, making them difficult to be effectively recognized by cell membrane ion channels, hindering efficient coupling with cardiomyocytes, and making it difficult to synergize with conductive hydrogels. This results in electrical stimulation being merely a non-specific electric field, significantly reducing modulation efficiency and targeting. Furthermore, inorganic piezoelectric materials have high rigidity, some contain toxic metal ions, and have poor biocompatibility. Organic piezoelectric materials, on the other hand, suffer from low piezoelectric coefficients and insufficient in vivo stability, making it difficult to meet the continuous electrical stimulation requirements for long-term myocardial infarction repair.
[0007] In nature, organisms such as electric eels construct ion gradients through specialized electrocytes, regulate ion polarization and depolarization processes, and generate high-intensity bioelectricity based on ion migration. Bioelectricity primarily takes the form of ionic current, and its essence is the transmembrane potential formed by the concentration difference of free ions across the cell membrane. The core elements of this process lie in the presence of freely moving ions and the interfacial environment. Anionic / cationic polyelectrolytes, composed of an immobile polymeric framework and freely migrating counterions, can generate significant asymmetric ion migration under mechanical stimulation, providing an ideal material basis for simulating bioelectric signals. Inspired by this, researchers have developed flexible sensing materials with mechano-ionic piezoelectric effects for real-time monitoring of various mechanical stimuli.
[0008] While the aforementioned studies have confirmed the feasibility of ion piezoelectric sensing, there is still significant room for improvement in piezoelectric output and sensing sensitivity. To address this, current research focuses on screening migrating ion species and constructing multilayer macroscopic confinement structures, with the core objective of optimizing material performance by enhancing ion mobility. Among these, the design of macroscopic confinement structures has attracted considerable attention due to its direct control pathway and significant effects. However, these structures essentially rely on interlayer ion concentration differences to drive ion migration, and their migration dynamics are limited by the physical scale of a single interface, making it difficult to achieve efficient local ion enrichment under weak mechanical excitations such as those found in the heart. Reducing the confinement scale from macroscopic to micrometer / nanometer levels allows for the construction of numerous uniformly dispersed phase interfaces within the material, increasing the density of ion migration channels per unit volume and improving local enrichment efficiency, thereby achieving a stronger piezoelectric response under weak stress conditions. Nevertheless, a systematic understanding of how microscopic confinement structures regulate ion migration dynamics remains lacking, and the relevant mechanisms are unclear, hindering the realization of stable and efficient ion electrical signals under weak excitations.
[0009] Therefore, how to achieve efficient and stable output of ion-electric signals under weak mechanical stimulation through reasonable micro-confined structure design has become a core problem that urgently needs to be solved in this field. In addition, due to constraints such as material biosafety, implantability compatibility, and injectable minimally invasive delivery, extending the application of ion piezoelectric effect from sensing and monitoring to tissue repair, especially in the field of cardiac tissue repair, faces new scientific and technological challenges. Summary of the Invention
[0010] To address the aforementioned shortcomings of existing technologies, this invention provides a piezoelectric hydrogel that promotes myocardial repair, its preparation method, and its applications. Based on the mechano-ionic piezoelectric effect, this invention synergistically achieves real-time monitoring and in-situ electrical stimulation repair of myocardial infarction. This invention integrates sensing and repair functions into the same material system, forming a cascaded coupled repair pathway of "mechanical sensing - ionic electroconversion - energy metabolism reprogramming - functional reconstruction." This overcomes the bottleneck of traditional conductive hydrogels and piezoelectric materials' inability to autonomously generate adaptive ionic electrical stimulation, providing a transformable new strategy for passive, in-situ, long-term treatment of myocardial infarction.
[0011] To achieve the above objectives, the technical solution adopted by the present invention to solve its technical problem is as follows: The purpose of this invention is to provide a method for preparing a piezoelectric hydrogel that promotes myocardial repair, comprising the following steps: (1) Sodium thioctic acid and thioctic acid were added to the dispersion of dopamine-modified oxidizing bacteria nanocellulose and stirred for 1-3 hours to obtain a prepolymerized liquid system with charge. (2) Add electrically neutral polyacrylamide microspheres to the prepolymer liquid system, continue stirring for 1-5 hours, then degas, and then let it stand at 30-35°C for 20-28 hours to obtain the piezoelectric hydrogel.
[0012] Further, in step (1), the mass ratio of sodium thioctic acid, thioctic acid and dopamine-modified oxidizing bacteria nanocellulose dispersion is 0.5~1:0.1~0.2:1~2; wherein, the mass fraction of dopamine-modified oxidizing bacteria nanocellulose dispersion is 1~3%.
[0013] Furthermore, the preparation method of the dopamine-modified oxidizing bacterial nanocellulose used in step (1) is as follows: S1. Add sodium periodate solution to bacterial nanocellulose aqueous dispersion, replace air with nitrogen and seal, react in the dark for 4-6 hours, and after the reaction is terminated, dialysis is used to purify and obtain oxidized bacterial nanocellulose. S2. Add the dopamine hydrochloride solution to the oxidizing bacterial nanocellulose solution and react in a vacuum and nitrogen atmosphere for 24-30 hours. After the reaction is completed, remove unreacted small molecule impurities by dialysis to obtain dopamine-modified oxidizing bacterial nanocellulose.
[0014] Further, the volume ratio of sodium periodate solution to bacterial nanocellulose aqueous dispersion is 0.5~1:1; the concentration of sodium periodate solution is 0.001~0.005 g / mL; and the content of bacterial nanocellulose in bacterial nanocellulose aqueous dispersion is 0.5~0.8 wt%. The volume ratio of dopamine hydrochloride solution to oxidizing bacterial nanocellulose solution is 0.1~0.5:1; the concentration of dopamine hydrochloride solution is 0.01~0.05 g / mL, and the concentration of oxidizing bacterial nanocellulose solution is 0.01~0.05 g / mL.
[0015] Furthermore, the preparation method of polyacrylamide microspheres is as follows: S1. Acrylamide, crosslinking agent and photoinitiator are added to the solvent and magnetically stirred until completely dissolved to obtain a homogeneous aqueous precursor solution; then an oil phase system is prepared using an emulsifier. S2. Based on the above aqueous precursor solution and oil phase system, water-in-oil microspheres are formed by using a microfluidic chip, and then acrylamide in the aqueous material is polymerized by ultraviolet light to form PAAM microspheres. S3. After polymerization, the oil phase is discarded, and the PAAM microspheres are dispersed in deionized water. Unreacted impurities are removed by dialysis to obtain polyacrylamide microspheres with uniform size and neutral charge.
[0016] Furthermore, the mass ratio of acrylamide, crosslinking agent and photoinitiator in S1 is 2~5:0.01~0.038:0.01~0.03.
[0017] Furthermore, the crosslinking agent used in S1 is N,N'-methylenebisacrylamide, the photoinitiator is α-ketoglutaric acid, and the emulsifiers are Span-20 and Span-80 in a mass ratio of 1:1~2.
[0018] Another object of the present invention is to provide a piezoelectric hydrogel that promotes myocardial repair, which is prepared by the above method.
[0019] Another object of the present invention is to provide the use of the above-described piezoelectric hydrogel in the preparation of a medicament that promotes myocardial repair.
[0020] Another object of the present invention is to provide the use of the above-described piezoelectric hydrogel in the preparation of a medicament for treating myocardial infarction.
[0021] The beneficial effects of this invention are: This invention utilizes the synergistic design of anion-cation asymmetric migration kinetics and microscopic confinement structures. Figure 1 This invention combines electrically neutral polyacrylamide microspheres with a charged sodium polythiooctanoate matrix, enabling them to generate endogenous ionic potentials driven by the mechanical energy of cardiac pulsation. This achieves in-situ, continuous electrical stimulation without external power source, and the conversion of mechanical energy into ionic signals, providing adaptive electrical stimulation for infarcted myocardium. It also synergistically enhances antioxidant and anti-inflammatory effects, efficiently repairing myocardial tissue and restoring electrophysiological function. This hydrogel possesses excellent mechanical stability, tissue adhesion, self-repair capability, and ionic piezoelectric properties (output voltage approximately 0.45 V at 50 kPa pressure). Furthermore, this invention overcomes the bottleneck of traditional conductive hydrogels and piezoelectric materials' inability to autonomously generate adaptive ionic electrical stimulation, providing a novel and convertible strategy for passive, in-situ, long-term treatment of myocardial infarction.
[0022] This invention reveals that the deep repair mechanism of the prepared piezoelectric hydrogel lies in activating the PI3K-Akt and calcium signaling pathways, systematically restarting energy metabolism networks such as the TCA cycle, respiratory chain, and mitochondrial translation, and simultaneously relieving cell cycle arrest, forming a cascaded coupled repair pathway of "mechanical sensing - ion-electric conversion - energy metabolism reprogramming - functional reconstruction". Attached Figure Description
[0023] Figure 1 This is a schematic diagram illustrating the efficient repair of myocardial infarction using the piezoelectric hydrogel prepared in this invention. Figure 2 This is a schematic diagram illustrating the design and preparation process of the piezoelectric hydrogel according to the present invention; Figure 3 The images show TEM images of the original BC and the dopamine-modified BC; where (A) is a transmission electron microscope image of BC; and (B) is a TEM image of OBC-DA. Figure 4 Images are presented using SEM and optical microscopy. (A) is a SEM image of PAAM microspheres; (B) is an optical microscopy image of the composite hydrogel with different PAAM microsphere area ratios (0.1-0.5); (C) is an image of the injectability test of the composite hydrogel; (D) is a SEM image of the pure PAAM-bacterial nanocellulose hydrogel matrix; (E) is a cross-sectional SEM image of the composite hydrogel; and (F) is a SEM image of the bottom surface of the composite hydrogel. Figure 5 The average surface potential of different hydrogel systems is shown in the graph. Figure 6 This is a photograph of the self-healing process of the composite hydrogel prepared according to the present invention. Figure 7 The diagram shows the adhesion performance of the composite hydrogel prepared in this invention; wherein, (A) is the adhesion diagram of the hydrogel on different biological tissues and material surfaces; and (B) is the statistical diagram of the adhesion strength of the hydrogel on different material surfaces. Figure 8 Impedance and conductivity measurements of hydrogels with different PAAM microsphere contents are shown in the figures. (A) shows the impedance curves of different hydrogels, and (B) shows the trend of ionic conductivity of the composite hydrogel as the PAAM microsphere content increases. Figure 9 The diagram shows the open-circuit voltage detection results of the piezoelectric sensor of the bilayer hydrogel; where (A) is the open-circuit voltage detection diagram of the bilayer hydrogel (sodium polythiooctanoate anionic hydrogel and electrically neutral PAAM hydrogel) under different pressures; (B) is the open-circuit voltage curve generated by pressing the hydrogel with a finger. Figure 10 The figures show the detection results of open-circuit voltage and short-circuit current of a piezoelectric sensor containing PAAM microspheres; (A) is a curve showing the change of open-circuit voltage with pressure after local pressing of the composite hydrogel; (B) is a peak open-circuit voltage detection figure for composite hydrogels with different PAAM microsphere contents; (C) is a response time test figure of the mechanical ion piezoelectric hydrogel at 50 kPa pressure; (D) is a short-circuit current curve at 50 kPa pressure. Figure 11 The piezoelectric response of the composite hydrogel containing PAAM microspheres under different mechanical stimulation methods is shown in the following graphs: (A) is the open-circuit voltage of the hydrogel under different tensile strains; (B) is the open-circuit voltage generated under ultrasonic mechanical stimulation (1 MHz, 5 W); and (C) is the open-circuit voltage curve measured when the hydrogel is attached to the surface of a rat heart. Figure 12The diagram illustrates the mechanism of the mechanical-ionic piezoelectric effect and shows the results of the finite element simulation. Figure 13 The images show the protective effects of different hydrogels on H9C2 cells stimulated by H2O2. (A) shows the live / dead cell staining of H9C2 cells after treatment with H2O2 (300 μM) for 2 hours and co-culture with different hydrogels for 24 hours; (B) shows the DCFH-DA staining of H9C2 cells after treatment with H2O2 (300 μM) for 2 hours and co-culture with different hydrogels for 24 or 72 hours; (C) shows the relative survival rate of H9C2 cells after treatment with different hydrogels for 24 and 72 hours; and (D) shows the quantitative analysis of DCFH fluorescence intensity. Figure 14 The images show the effects of different hydrogels on promoting endothelial cell migration, proliferation, and angiogenesis. Among them, (A) is a bright field image of scratch healing: HUVECs treated with different hydrogels for 0 hours and 12 hours; (B) is a fluorescence staining image of HUVECs in vitro tube formation experiment; (C) is a migration rate detection image of HUVECs after different hydrogel treatments; and (D) is a quantitative analysis image of total blood vessel length under different hydrogel treatment conditions. Figure 15 The images show the detection of the piezoelectric hydrogel prepared in this invention on the repair of infarcted myocardium; (A) is a representative echocardiogram of the heart of rats in different treatment groups; (B) is a detection image of cardiac function indicators, including ejection fraction (EF), fractional shortening (FS), end-diastolic volume (EDV) and end-systolic volume (ESV), on days 14 and 28 after treatment. Figure 16 The images show the electrocardiogram (ECG) changes of the piezoelectric hydrogel prepared in this invention during the repair of infarcted myocardium; (A) is the ECG recording after myocardial infarction modeling; (B) is the ECG of each group after 28 days of treatment; and (C) is the statistical analysis of QRS duration. Figure 17 The images show the fluorescence staining of infarcted myocardium and the quantitative analysis of myocardial infarction area. Among them, (A) shows the hematoxylin-eosin (H&E) staining and Masson trichrome staining of infarcted myocardium in each group after 28 days of treatment; (B) shows the quantitative analysis of the wall thickness of the left ventricular infarction area in each group (n=8); and (C) shows the quantitative analysis of the myocardial infarction area in each group (n=8). Figure 18 The images show the detection of macrophage types after treatment with the piezoelectric hydrogel prepared in this invention; (A) is an immunofluorescence co-staining image of Arg-1 (red) and iNOS (green); (B) is a quantitative analysis image of fluorescence intensity in the iNOS positive region; and (C) is a quantitative analysis image of fluorescence intensity in the Arg-1 positive region. Figure 19 The image shows the effect of the piezoelectric hydrogel prepared in this invention on angiogenesis; (A) is an immunofluorescence co-staining image of CD31 and α-SMA; (B) is a quantitative analysis image of the positive density of CD31 / α-SMA. Figure 20 The images show the effects of the piezoelectric hydrogel prepared in this invention on myocardial electrical conduction and contractile function; (A) is a co-staining image of CX43 and α-actinin immunofluorescence; (B) is a quantitative analysis image of the number of CX43 positive cells; and (C) is a quantitative analysis image of the number of α-actinin positive cells. Detailed Implementation
[0024] The specific embodiments of the present invention are described below to enable those skilled in the art to understand the present invention. However, it should be understood that the present invention is not limited to the scope of the specific embodiments. For those skilled in the art, various changes are obvious as long as they are within the spirit and scope of the present invention as defined and determined by the appended claims. All inventions utilizing the concept of the present invention are protected.
[0025] The materials used in this invention are sourced from the following sources: Bacterial nanocellulose dispersion (BC, 0.8%, diameter 50-100 nm, length >20 μm) was purchased from Guilin Qihong Technology Co., Ltd. Dopamine hydrochloride (DA, purity >99.0%) and sodium periodate (purity >99.0%) were purchased from Adamas Reagent Co., Ltd. Lipoic acid (LA, purity ≥99.0%) and sodium lipoate (ST, purity ≥98.0%) were purchased from Shanghai Adamas Reagent Co., Ltd. Acrylamide (AAM, purity ≥99.5%), N,N'-methylenebisacrylamide (purity ≥99.5%), and α-ketoglutaric acid (purity 99.0%) were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. The microfluidic chip was designed and manufactured by Harbin Taoshu Biotechnology Co., Ltd. Dialysis bags (3500 Da) were purchased from Shanghai Maclean Biochemical Technology Co., Ltd. All aqueous solutions were prepared using deionized water (DI water).
[0026] Example 1 A biphase gradient ionic piezoelectric hydrogel that promotes myocardial repair is prepared as follows (see process). Figure 2 ): (1) Preparation of OBC-DA bacterial nanocellulose 100 mL of bacterial nanocellulose (BC) aqueous dispersion was transferred to a three-necked flask, followed by the addition of 100 mL of an aqueous solution containing 0.4 g of sodium periodate. The system was then purged with nitrogen to remove air and sealed, and reacted at a constant temperature for 4 h under light-protected conditions. After the reaction was complete, an appropriate amount of ethylene glycol was added to quench any unreacted sodium periodate to terminate the reaction. The reaction solution was then transferred to a dialysis bag for dialysis purification, ultimately yielding oxidized bacterial nanocellulose (OBC).
[0027] 1 g of OBC was weighed and dispersed in 100 mL of deionized water, transferred to a three-necked flask, and then 10 mL of an aqueous solution containing 0.2 g of dopamine hydrochloride (DA) was added. The system was repeatedly evacuated using an oil pump to completely remove oxygen. Once a vacuum-free state was achieved, nitrogen gas was introduced for protection, and the reaction was continued for 24 h. After the reaction was complete, the mixture was dialyzed using a dialysis bag with a molecular weight cutoff of 3500 Da to remove unreacted small molecule impurities, ultimately yielding dopamine-modified oxidizing bacterial nanocellulose (OBC-DA).
[0028] (2) Preparation of PAAM microspheres S1. Prepare the precursor solution in a brown sample vial. Accurately weigh 5 g of acrylamide (AAM, monomer), 0.0375 g of N,N'-methylenebisacrylamide (crosslinking agent), and 0.01 g of α-ketoglutarate (photoinitiator), and add them sequentially to 25 g of deionized water. Stir magnetically until completely dissolved to obtain a homogeneous aqueous precursor solution (store away from light to prevent premature decomposition of the photoinitiator). Then prepare the oil phase system: weigh 0.4 g of Span-20 and 0.8 g of Span-80 emulsifiers, add them to 50 mL of cyclohexane, and ultrasonically disperse in an ultrasonic cleaner for 10 min to ensure complete dissolution of the emulsifiers and the formation of a homogeneous and stable oil phase system.
[0029] S2. Preparation of water-in-oil (W / O) microspheres using microfluidic chips. The aqueous precursor solution and oil phase system were separately loaded into syringes and precisely injected into the corresponding channels of the microfluidic chip using a microinjection pump (recommended flow rate: aqueous phase 5-10 μL / min, oil phase 50-100 μL / min). Uniform water-in-oil microspheres were formed using the shearing action of the fluid within the chip. Microsphere polymerization and post-treatment: The water-in-oil microsphere emulsion collected at the chip outlet was placed under a UV polymerizer (wavelength 365 nm) for 30 min to initiate polymerization, causing the AAM monomers in the aqueous phase to crosslink and polymerize to form PAAM polymer microspheres. After polymerization, the microspheres were collected by centrifugation (3000 rpm, 10 min), and the upper oil phase was discarded. The microspheres were redispersed in deionized water and transferred to a dialysis bag with a molecular weight cutoff of 3500 Da. Dialysis was performed continuously for 48 h using deionized water as the dialysis medium to thoroughly remove unreacted monomers, residual initiators, and small molecule impurities. Uniform PAAM neutral microspheres were finally obtained.
[0030] (3) Synthesis of hydrogels A 1% (w / w) aqueous dispersion of dopamine-modified oxidizing bacterial nanocellulose (OBC-DA) was prepared under light-protected conditions and set aside. Subsequently, 1.0 g of sodium lipoate (ST) and 0.2 g of lipoic acid (LA) were accurately weighed and added to 2 g of the above OBC dispersion. The mixture was placed on a magnetic stirrer (300 rpm) and stirred continuously for 1 h. A viscous prepolymer system was obtained through the ring-opening polymerization of the disulfide ring of lipoic acid.
[0031] Next, an appropriate amount of PAAM microspheres were added to the prepolymer solution, and the magnetic stirring speed was adjusted to 100 rpm for low-speed mixing for 2 hours. After stirring, the mixture was ultrasonically treated for 10 minutes to completely remove air bubbles. Finally, the degassed mixture was transferred to a sealed container and placed at a constant temperature of 35°C for 24 hours. Through oxidative cross-linking within the system, a three-dimensional network structure of polymeric composite hydrogel was finally formed.
[0032] Example 2 The dopamine-modified cellulose nanoparticles, PAAM microspheres, and piezoelectric hydrogels prepared in Example 1 were tested, as follows: 1. Morphology of dopamine-modified bacterial nanocellulose (BC) was observed using transmission electron microscopy (TEM, Talos F200S). TEM images ( Figure 3 As shown in Figures A and B, the modified BC surface is coated with a distinct dopamine oxidative crosslinking layer.
[0033] 2. Analysis of electrically neutral PAAM microspheres revealed a significantly narrower particle size distribution compared to traditional emulsion polymerization methods, and the internal structure exhibited a porous hydrogel three-dimensional network structure. Figure 4 (A). Thanks to their uniform size, PAAM microspheres can be uniformly integrated into the sodium polythiooctanoate hydrogel matrix without significant aggregation. By adjusting the amount of microspheres added, a series of composite hydrogels with a microsphere-to-matrix planar area ratio of 0.1 to 0.5 can be obtained. Figure 4 (B) The sample has good injectability. Figure 4 (C)
[0034] 3. Scanning electron microscopy (SEM) observation showed that the pure sodium polythiooctanoate-bacterial nanocellulose hydrogel formed a continuous three-dimensional network framework. Figure 4 (D). Cross-sectional SEM images of the composite hydrogel further show that PAAM microspheres are uniformly dispersed in the hydrogel matrix. Figure 4 (E). Notably, microspheres protrude from the matrix surface at the bottom of the composite hydrogel. Figure 4 The F-value indicates that the microspheres can directly contact the substrate tissue after injection, which provides a favorable structural basis for the formation of a local potential difference at the interface under mechanical stimulation.
[0035] 4. To verify the design of the "electrically neutral microsphere-charged matrix" two-phase ion gradient structure, Kelvin probe force microscopy (KPFM) was used to characterize the surface potential distribution of each component. The results showed that the pure sodium polythiooctanoate hydrogel film exhibited significant negative charge characteristics, with a local surface potential reaching -109.1 mV. Figure 5 The electrically neutral PAAM film showed almost no detectable potential signal. This directly confirms that the sodium polythiooctanoate network acts as an ion diffusion source carrying transferable charges, while the PAAM microspheres maintain electrical neutrality as an inert ion diffusion phase. These results successfully validate the two-phase ion gradient structure designed in this invention: the sodium polythiooctanoate network provides a stable negative charge background, and the PAAM microspheres act as locally electrically neutral regions; together, they construct an ion piezoelectric basis that can respond to mechanical stimuli and generate local potential differences.
[0036] Example 3 The self-healing and adhesion functions of the piezoelectric hydrogel prepared in Example 1 were tested using a rotational rheometer (Anton Paar, MCR302). The dynamic rheological properties of the hydrogel were measured using an electronic universal testing machine at 10 mm / min. -1 Shear adhesion tests were conducted using the peel speed, and the adhesion strength was calculated using the ratio of "maximum load / adhesion area". For example... Figure 6 As shown, when the hydrogel is cut and the cut surfaces are brought back into contact, the material quickly bonds together and returns to its original complete shape, and its tensile strength and flexibility are also restored simultaneously.
[0037] Besides its self-healing properties, reliable tissue adhesion is the core guarantee for the efficient signal transmission and therapeutic function of hydrogel cardiac patches. The piezoelectric hydrogel prepared in this invention, rich in carboxyl and catechol groups, exhibits broad-spectrum and stable interfacial adhesion properties. Tests show that this hydrogel also has good adhesion effects on biological tissues such as rat heart, liver, spleen, lung, kidney, and muscle, as well as on the surfaces of polymeric and inorganic materials. Figure 7 (A). Further testing revealed that its adhesion to various substrates was not less than 13 kPa. Figure 7 (B), further verifying its universality of adhesion.
[0038] Example 4 The piezoelectric hydrogel prepared in Example 1 was subjected to ion piezoelectric performance testing. The cyclic voltammetry (CV) curve and electrochemical impedance (EIS) of the material were measured using an electrochemical workstation (PMCCH808A, Princeton Applied Research). The conductivity of the hydrogel was calculated based on the impedance data. The EIS test parameters were set as follows: frequency scan range of 0.01~100,000 Hz.
[0039] 2.0 1.5 0.5 cm 3 A piezoelectric hydrogel is constructed by using copper foil as collectors at the top and bottom, and then encapsulating and fixing it with 3M elastic tape; or a 2.0... 1.5 0.25cm 3 Sodium polythiooctanoate hydrogel with 2.0 1.5 0.25cm 3 The polyacrylamide hydrogel was assembled into two layers, and then further assembled with copper foil and elastic tape. During testing, the sensor was subjected to cyclic pressures of 0–50 kPa, cyclic tensile stresses of 0–60%, and handheld ultrasound (1 MHz frequency, 5 W power), and the dynamic changes in open-circuit voltage and short-circuit current were recorded. In vivo piezoelectric signal acquisition involved implanting the sensor onto the surface of an infarcted heart, and recording the dynamic changes in open-circuit voltage through the heart's beating motion. Specific results are as follows: like Figure 8 As shown in Figure A, the electrically neutral PAAM hydrogel exhibits high impedance characteristics, indicating that there are almost no migrating ions inside it; the impedance of the composite hydrogel is significantly reduced, decreasing by about an order of magnitude compared to PAAM. Further calculations of ionic conductivity revealed that the conductivity of the composite hydrogel gradually decreases with increasing PAAM microsphere content. Figure 8(See Figure B). When the proportion of PAAM microspheres was 1 / 10 (HPS-0.1), the ionic conductivity of the composite hydrogel reached 12.5 ± 0.39 S / m, significantly higher than the inherent conductivity range of human heart tissue (approximately 0.3~0.7 S / m). This property is expected to effectively compensate for the electrophysiological conduction function of damaged myocardial regions, providing a favorable electrical microenvironment for myocardial repair.
[0040] To evaluate the mechano-ionic piezoelectric response of the material, we first constructed a piezoelectric sensor based on a bilayer hydrogel, with conductive copper foil attached as electrodes to the upper and lower surfaces of the hydrogel. Figure 9 (Illustration of A in the middle). For example... Figure 9 As shown in Figure A, when pressure is applied to the sensor, the open-circuit voltage gradually increases; after the pressure is removed, the voltage returns to its initial level. The peak output voltage increases with increasing applied pressure, producing an open-circuit voltage of approximately 0.45 V at a pressure of 50 kPa. Furthermore, pressing with a finger also produces a distinct peak voltage curve. Figure 9 (B) This visually confirms that the hydrogel has excellent mechanical-ionic piezoelectric conversion capabilities.
[0041] A piezoelectric sensor was further constructed using a composite hydrogel containing PAAM microspheres, and conductive copper foil was attached to both ends of the gel for testing. The results showed that as the applied pressure increased from 2.5 kPa to 50.0 kPa, the peak open-circuit voltage gradually increased from approximately 0.03 V to 0.16 V, exhibiting a good pressure-voltage response relationship. Figure 10 (A). This result verifies that the microscopic ion gradient confinement structure formed by PAAM microspheres and anionic hydrogel matrix can effectively generate local ion potentials under mechanical stimulation.
[0042] To theoretically elucidate this phenomenon, we introduce the Poisson-Nernst-Planck equation to describe the coupling process of ion transport and electrostatic potential construction in hydrogels. This theoretical model shows that the output voltage of the composite hydrogel under mechanical stimulation can be expressed as: (1) in, Where N is the output voltage and N is the number of ions. It is the ionic conductivity. and This represents the volume of anions and cations. and The flow rates of anions and cations in the hydrogel. This represents the pressure gradient inside the hydrogel.
[0043] According to the theoretical model, the piezoelectric output potential of the hydrogel is positively correlated with the ion concentration, the difference between the product of the cation and anion charge ratios, and the internal pressure gradient, and negatively correlated with the material's conductivity. Therefore, the piezoelectric output can be effectively optimized by controlling the ion concentration and pressure gradient distribution. This invention introduces electrically neutral PAAM microspheres into an anionic sodium polythiooctanoate hydrogel matrix to construct a localized microscopic ion gradient confinement structure, thereby enhancing the internal pressure gradient distribution under mechanical stimulation.
[0044] like Figure 10 As shown in Figure B, the pure PAAM hydrogel exhibits no open-circuit voltage under pressure, confirming the lack of mobile ions in its neutral network. The open-circuit voltage of the piezoelectric hydrogel initially increases and then decreases with increasing PAAM microsphere content. When the PAAM content is 3 / 10 (HPS-0.3), the system achieves optimal piezoelectric output, with a peak open-circuit voltage of 0.16 ± 0.0069 V. This indicates that at this ratio, the sodium polythiooctanoate network provides free-moving Na+. + The content is optimally matched with the ion-confined structure constructed by the microspheres, maximizing the difference in migration rates between anions and cations and the local pressure gradient.
[0045] Further evaluation of the response kinetics of HPS-0.3 sample under 50 kPa pressure. Figure 10 The results from C show that the open-circuit voltage reaches its peak value approximately 0.5 s after pressure is applied, and essentially returns to its initial level within approximately 1.0 s after pressure is removed, indicating that the system possesses a rapid mechano-ionic response capability. In addition to the open-circuit voltage, the composite hydrogel sensor also generates a stable short-circuit current peak under periodic pressure stimulation. Figure 10 The test (D) further confirms its mechanical-ion piezoelectric conversion capability. Notably, the sensor maintained a stable piezoelectric signal output during 1000 cycles of pressurization testing, demonstrating excellent cyclic stability and ensuring its long-term reliable application in dynamic physiological environments.
[0046] In addition to pressure response, this sensor exhibits sensitive piezoelectric conversion capabilities to various mechanical stimulation modes. For example... Figure 11 As shown in Figure A, under tensile strain stimulation ranging from 10% to 50%, the open-circuit voltage increases linearly with increasing strain. Furthermore, under ultrasonic mechanical stimulation at 1 MHz and 5 W, the composite hydrogel can generate periodic open-circuit voltage fluctuations of approximately 0.2 V, and the output voltage exhibits a regular response to changes in ultrasonic frequency. Figure 11 (B). The above results show that this material can convert various forms of mechanical input into ionic potential signals, exhibiting a broad-spectrum mechano-ionic piezoelectric effect.
[0047] To verify its practical application potential in physiological environments, the composite hydrogel was attached to the surface of the heart in a rat model of myocardial infarction, and its piezoelectric output under complex cardiac stimulation was monitored in real time. Figure 11 As shown in Figure C, the open-circuit voltage signal exhibits stable periodic fluctuations with heart rate, with a maximum output voltage of approximately 50 mV. This result confirms that the local mechanical stimulation generated by cardiac pulsation can be effectively converted into an electrical signal by the hydrogel, providing crucial experimental evidence for its application in in-situ autonomous mechanical piezoelectric modulation of myocardial repair.
[0048] In its initial state without mechanical stimulation, the hydrogel as a whole does not deform, and the internal ions are in a uniformly distributed equilibrium state, with no ion gradient or potential difference generated. At this time, the carboxylate anions (COO-) in the sodium polythiooctanoate (PST) hydrogel matrix... - ) and counteracting sodium ions (Na + The PAAM microspheres are uniformly distributed and electrically neutral, containing no ions. The entire system exhibits macroscopic electronegativity, and its potential can be considered as the reference potential φ0. When the composite hydrogel is subjected to mechanical stimulation such as pressing or stretching, significant local deformation occurs in the compressed area. During this process, the PST polymer network contracts or stretches, leading to the release of fixed carboxylate anions (COO-) from the chains. - Sodium ions (Na+) aggregate as chain segments shift, while freely moving sodium ions (Na+)... + Then, directional migration occurs under mechanical force. Because a large number of uncharged PAAM microspheres are uniformly dispersed within the hydrogel, these microspheres act as physical interfaces, providing a Na+ environment. + This provides preferential aggregation sites, allowing Na+ in the compressed region to... + A large amount of Na migrates to the PAAM microspheres, forming a locally positively charged enrichment region, while the PST matrix side forms a negatively charged region due to the aggregation of anions. This ion rearrangement results in the formation of a directionally aligned microscopic electrical double layer at the interface between each PAAM microsphere and the PST matrix: the PAAM side is enriched with Na. + (Positively charged layer), COO enriched on the PST side - (Negative layer) Figure 12 Within the pressure zone, the orientation of the electric double layer of all PAAM microspheres is determined by the pressure direction, exhibiting a highly consistent arrangement. The electric fields of countless microscopic electric double layers (E1, E2, …, E…) n The synergistic superposition of these forces creates a macroscopic equivalent electric field E= Ultimately, due to the synergistic polarization effect, the overall potential on the pressing side deviates from the reference value. The unpressed side (which remains electrically neutral and at the reference potential) A measurable macroscopic potential difference is formed between them. The voltage output can be directly detected by an external voltmeter. This process perfectly illustrates the essence of mechanical-ion piezoelectricity: without external charge injection, it achieves a reversible conversion of mechanical energy into electrical energy solely through mechanical force-driven ion rearrangement and interface polarization.
[0049] Example 5 The in vitro iontophoresis repair capacity of the piezoelectric hydrogel prepared in Example 1 was tested, as follows: This invention employs a hydrogen peroxide (H2O2)-induced oxidative stress model in H9C2 cells. The protective effect of each hydrogel group against H2O2-stimulated H9C2 cells was evaluated using Live / Dead cell staining. Figure 13 (A and C). After 72 h of treatment, some cells died in the H2O2 group, while all hydrogel groups maintained a high proportion of viable cells. Intracellular ROS levels were detected using the DCFH-DA fluorescent probe. Figure 13 (B and D). The control group had extremely low ROS content, while the H2O2 group accumulated a large amount. Thanks to the antioxidant activity of the lipoic acid group, the ROS levels of the Hydrogel-1 and Hydrogel-2 groups were 28.44% and 35.16%, respectively, both significantly lower than those of the H2O2 group (set as 100%).
[0050] Insufficient vascularization is another key factor hindering myocardial infarction repair, making angiogenesis an important treatment strategy. We first assessed the proliferation and migration capabilities of human umbilical vein endothelial cells (HUVECs). Scratch assay ( Figure 14 As shown in Figures A and C, after 12 h of treatment, the scratches in the Hydrogel-2 group (with its ion-piezoelectric properties) were almost completely closed, with a migration rate of 96.41%; while the blank group and the Hydrogel-1 group still had obvious unhealed areas. This indicates that the ion-electric stimulation generated by the hydrogel can effectively promote endothelial cell migration and proliferation. Furthermore, we used the HUVEC tube formation assay to evaluate its angiogenesis-promoting ability (…). Figure 14 (Group B). Compared to other groups, Hydrogel-2 significantly promoted the formation of tubular structures. Quantitative analysis was performed on total length, number of connection points, number of branches, and number of pores. Figure 14 The results showed that all indicators in the Hydrogel-2 group were significantly higher than those in the blank group and the Hydrogel-1 group, confirming that ion-piezoelectric hydrogel-mediated electrical stimulation can effectively promote angiogenesis.
[0051] Example 6 The piezoelectric hydrogel prepared in Example 1 was used to test myocardial infarction repair. All experimental animals were purchased from Beijing Vital River Laboratory Animal Technology Co., Ltd. Animal experiments were approved by the Animal Ethics Committee of West China Hospital, Sichuan University. The acute myocardial infarction model was established by permanent ligation of the left anterior descending coronary artery (LAD). First, male Sprague-Dawley (SD) rats weighing 150g were anesthetized using a combination of a small animal ventilator and a gas anesthesia machine with isoflurane. In a sterile environment, the shaved rats' limbs and incisors were fixed to a surgical board, and then the subcutaneous tissue and muscles in the middle of the neck were incised to fully expose the trachea. The trachea was then quickly intubated and connected to the small animal ventilator, and the ventilator parameters were adjusted (respiratory rate: 60 breaths / min, tidal volume: 10 ml / min: 60 breaths / min, tidal volume: 3 ml / 100g, respiratory ratio: 1:1.5), while the rats' condition was monitored in real time. Next, an incision was made at the fourth and fifth ribs on the left side of the rat's chest, the pericardium was torn open, and the heart and blood vessels were exposed. The left anterior descending coronary artery was ligated with sutures approximately 0.5 mm deep, 2-3 mm from the pulmonary artery cone and the lower edge of the left auricle. Electrocardiogram monitoring showed significant ST-T segment elevation, confirming the successful establishment of the rat myocardial infarction model.
[0052] Rats with a myocardial infarction model were randomly divided into three groups: a myocardial infarction control group (MI), a hydrogel group without conductive material (Hydrogel-1), and a CSCH group (Hydrogel-2). Subsequently, an appropriate amount of hydrogel was applied to the surface of the heart, and medical tape was used to help fix and protect the hydrogel. The rats' thoracic cavities were then sutured, and after ensuring no abnormalities, the rats were transferred to other locations for rearing.
[0053] The piezoelectric hydrogel designed in this invention can achieve mechano-ionic piezoelectric conversion through mechanically driven ion migration without external charge injection. In a pathological model of myocardial infarction, the infarcted area experiences significantly weakened local mechanical stimulation due to scar tissue formation, resulting in a clear difference in the mechanical microenvironment compared to normal myocardial tissue. This pathological characteristic provides an ideal physiological application scenario for in-situ electrical stimulation therapy based on the mechano-ionic piezoelectric effect. Figure 15 (A). After the hydrogel is attached to the surface of the heart, the difference in mechanical force between normal myocardium and the infarcted area can be used to efficiently convert and form a local ionic potential difference. Through in-situ electrical stimulation, the function of the infarcted myocardium can be repaired, thereby restoring the synchronous contraction characteristics and normal electrophysiological function of the heart.
[0054] Based on the above design principles, the repair effect of the hydrogel cardiac patch was verified in a rat model of myocardial infarction. The composite hydrogel was attached to the surface of the infarcted heart. Echocardiography was used to assess cardiac function parameters, including ejection fraction (EF), fractional shortening (FS), end-diastolic volume (EDV), and end-systolic volume (ESV), 14 and 28 days after treatment. Left ventricular end-diastolic volume (EDV) and left ventricular end-systolic volume (ESV) were measured using the disc two-plane method (modified Simpson's rule). The formulas for calculating the left ventricular ejection fraction (EF) and fractional shortening (FS) in rats were: EF = ((EDV - ESV) / EDV) × 100%, FS = ((EDD - ESD) / EDD) × 100%. Here, ESD represents the left ventricular end-diastolic size, and ESD represents the left ventricular end-systolic size. Furthermore, electrocardiograms were collected from rats at 7, 14, and 28 days post-surgery.
[0055] Figure 15 The results from the B study showed that, compared with the Sham group, the MI model group rats had significantly lower EF and FS, and higher EDV and ESV, exhibiting typical pathological features of myocardial infarction. Compared with the MI group, the Hydrogel-1 group, which only has ionic conductivity and no piezoelectric effect, showed improved EF and FS, and partially improved EDV and ESV, indicating that its ionic conductivity can reduce scar tissue resistance to a certain extent and delay the pathological deterioration process. Notably, the Hydrogel-2 group, which has a mechanopiezoelectric effect, showed the most significant therapeutic effect: EF increased from 48.38 ± 3.29% to 82.25 ± 4.84%, FS increased from 22.40 ± 2.32% to 51.53 ± 3.60%; EDV decreased from 0.97 ± 0.07 mL to 0.40 ± 0.03 mL, and ESV decreased from 0.55 ± 0.03 mL to 0.06 ± 0.02 mL. The above results indicate that the introduction of the mechano-ionic piezoelectric effect can significantly improve the contractile function and ventricular remodeling of the infarcted heart, confirming that the hydrogel can achieve myocardial repair through in-situ mechano-electric conversion, providing a new strategy for passive electrical stimulation therapy of myocardial infarction.
[0056] To further elucidate the self-induced bioelectric stimulation therapeutic mechanism of this piezoelectric hydrogel, we dynamically monitored changes in electrocardiograms (ECGs) at different time points post-surgery and systematically evaluated its regulatory efficacy on cardiac electrophysiological homeostasis. For example... Figure 16 As shown in Figure A, immediately after ligation of the left anterior descending artery (LAD) in rats, the ECG showed ST segment elevation with a convex upward sloping and T wave height, confirming the successful establishment of the acute myocardial infarction model. From 7 to 28 days post-surgery, the ECG of the simple infarction group (MI group) showed pathological Q waves and T wave inversion; with disease progression, the depth of the Q wave and the degree of T wave inversion continued to worsen. Figure 16(B), and the QRS group duration is significantly prolonged ( Figure 16 (C) This electrophysiological evolution indicates that electrodecoupling fibrosis in the infarct region alters the ion channel properties of myocardial cell membranes, leading to a severe delay in depolarization and repolarization processes, exhibiting typical characteristics of electro-ion coupling imbalance. Compared to the MI group, Hydrogel-1, which only possesses ion-conducting function, can partially compensate for the electrical conduction barrier in the fibrotic scar region, delaying pathological electrophysiological remodeling and shortening the QRS complex duration to some extent. Notably, Hydrogel-2, which possesses mechanopiezoelectric effects, exhibits the best electrophysiological repair effect: it not only significantly reduces ST segment elevation amplitude but also continuously shortens the QRS complex duration from 51.0 ± 6.3 ms to 24.0 ± 3.2 ms, essentially restoring it to near-normal levels. Its core mechanism lies in the fact that, under the physiological mechanical stimulation generated by the periodic contraction and relaxation of the heart, the hydrogel generates a biomimetic endogenous ion voltage in situ at the mechanical gradient region at the junction of the infarct area and normal myocardium. Through the synergistic effect of ion-electric coupling and electrical stimulation, it effectively reconstructs the cardiac electrical conduction pathway and electrophysiological homeostasis.
[0057] To visually assess the effectiveness of myocardial tissue repair and the degree of ventricular remodeling, rats were euthanized on postoperative days 14 and 28. Anesthetized rats underwent rapid thoracotomy to remove the heart. The heart was repeatedly rinsed with PBS buffer to remove residual blood, and then fixed in tissue fixative. Heme-eosin (H&E) and Masson's trichrome staining methods were used to assess cardiac morphology and infarct area. After paraffin sectioning, dewaxing, hydration, staining, dehydration, and mounting, H&E and Masson stained images were observed and acquired using an upright optical microscope (Nikon Eclipse E100). Finally, ImageJ image analysis software was used to calculate the infarct area and left ventricular wall thickness.
[0058] like Figure 17 As shown in Figure A, typical pathological ventricular remodeling after myocardial infarction is characterized by thinning of the ventricular wall in the infarct area, destruction of normal myocardial structure, and extensive collagen fiber deposition. Quantitative analysis using H&E staining showed that the ventricular wall thickness in the infarct area of the MI group was only 816.36 ± 84.49 μm; the Hydrogel-1 group, which only possesses ionic conductivity, had limited inhibitory effect on ventricular wall thinning; while the Hydrogel-2 group, which possesses mechanopiezoelectric effects, significantly resisted pathological remodeling, with its left ventricular wall thickness in the infarct area increasing to 2874.73 ± 453.63 μm. Figure 17 (Middle B). Masson trichrome staining results further revealed differences in the regulation of collagen deposition: compared with the MI group and the Hydrogel-1 group, the Hydrogel-2 group retained more red myocardial fibers, while blue collagen fiber deposition was significantly reduced ( Figure 17(A). Quantitative analysis showed that Hydrogel-2 could effectively inhibit the expansion of infarct size and the progression of fibrosis, significantly reducing the myocardial infarction area from 57.33 ± 3.05% to 6.33 ± 1.53% ( ). Figure 17 (C)
[0059] The above results demonstrate that in-situ ionoelectric stimulation of the mechano-ionic piezoelectric hydrogel can effectively inhibit excessive collagen deposition and maintain the mechanical integrity of the ventricular wall through a synergistic mechanism of "promoting myocardial survival and proliferation and inhibiting fibroblast activation," providing a crucial morphological basis for cardiac function recovery. Our self-driven mechano-ionic piezoelectric hydrogel simultaneously achieves structural repair and electrophysiological function reconstruction of infarcted myocardial tissue.
[0060] Example 7 To explore the pathway by which the piezoelectric hydrogel prepared in this invention repairs the myocardium through in-situ electrical stimulation, we conducted research from the perspectives of immune microenvironment remodeling, angiogenesis, and myocardial electrical conduction and contractile function.
[0061] 1. Immune microenvironment remodeling and macrophage polarization Macrophages, as core effector cells in the immune response following myocardial injury, play a crucial role in the repair process through the regulation of their phenotypic polarization. For example... Figure 18 As shown in Figures A, B, and C, compared to the MI and Hydrogel-1 groups, the Hydrogel-2 group exhibited a significant decrease in iNOS-positive M1 pro-inflammatory macrophages and a significant increase in Arg-1-positive M2 repair macrophages. This result indicates that in situ electrical stimulation by mechano-ionic piezoelectric hydrogels can effectively drive macrophage polarization towards a repair phenotype, inhibit excessive inflammatory responses, and create a favorable immune microenvironment for tissue repair.
[0062] 2. Promotes angiogenesis Results of staining for angiogenesis-related markers CD31 and α-SMA ( Figure 19 The results (A and B) showed that the proportion of positive cells in the Hydrogel-2 group was significantly higher than that in other groups, confirming that it can effectively promote angiogenesis in the peri-infarct area and provide a structural basis for the restoration of blood supply to damaged myocardium.
[0063] 3. Restore myocardial electrical conduction and contractile function Connexin 43 (CX43) is a key gap junction protein that determines the efficiency of myocardial electrical conduction, while α-actinin is a structural protein that maintains synchronous myocardial contraction. Immunofluorescence staining results ( Figure 20Figures A and B show that CX43 expression was significantly downregulated in the MI group (0.37 ± 0.07%), suggesting impaired electrical communication between cardiomyocytes; CX43 expression was significantly upregulated to 20.05 ± 0.58% in the Hydrogel-2 group. α-actinin expression was weak in the MI group, but most significantly expressed in the Hydrogel-2 group. Figure 20 (C). The principle is that the mechanical-ionic piezoelectric hydrogel forms a biomimetic ion potential in situ in the infarct area through the directional migration of ions driven by the heartbeat, regulates the homeostasis of myocardial cell membrane potential, activates related ion channels and signaling pathways, promotes CX43 synthesis and membrane localization and α-actinin expression, thereby restoring the electro-contraction coupling function of myocardium.
[0064] Finally, it should be noted that the above specific embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications and substitutions should be covered within the scope of the claims of the present invention.
Claims
1. A method for preparing a piezoelectric hydrogel that promotes myocardial repair, characterized in that, Includes the following steps: (1) Sodium thioctic acid and thioctic acid were added to the dispersion of dopamine-modified oxidizing bacteria nanocellulose and stirred for 1-3 hours to obtain a prepolymerized liquid system with charge. (2) Add electrically neutral polyacrylamide microspheres to the prepolymer liquid system, continue stirring for 1-5 hours, then degas, and then let it stand at 30-35°C for 20-28 hours to obtain the piezoelectric hydrogel.
2. The preparation method according to claim 1, characterized in that, In step (1), the mass ratio of sodium thioctic acid, thioctic acid and dopamine-modified oxidizing bacteria nanocellulose dispersion is 0.5~1:0.1~0.2:1~2; wherein, the mass fraction of dopamine-modified oxidizing bacteria nanocellulose dispersion is 1~3%.
3. The preparation method according to claim 1, characterized in that, The preparation method of dopamine-modified oxidizing bacterial nanocellulose used in step (1) is as follows: S1. Add sodium periodate solution to bacterial nanocellulose aqueous dispersion, replace air with nitrogen and seal, react in the dark for 4-6 hours, and after the reaction is terminated, dialysis is used to purify and obtain oxidized bacterial nanocellulose. S2. Add the dopamine hydrochloride solution to the oxidizing bacterial nanocellulose solution and react in a vacuum and nitrogen atmosphere for 24-30 hours. After the reaction is completed, remove unreacted small molecule impurities by dialysis to obtain dopamine-modified oxidizing bacterial nanocellulose.
4. The preparation method according to claim 3, characterized in that, The volume ratio of sodium periodate solution to bacterial nanocellulose aqueous dispersion is 0.5~1:1; the concentration of sodium periodate solution is 0.001~0.005 g / mL; the content of bacterial nanocellulose in bacterial nanocellulose aqueous dispersion is 0.5~0.8 wt%. The volume ratio of dopamine hydrochloride solution to oxidizing bacterial nanocellulose solution is 0.1~0.5:1; the concentration of dopamine hydrochloride solution is 0.01~0.05 g / mL, and the concentration of oxidizing bacterial nanocellulose solution is 0.01~0.05 g / mL.
5. The preparation method according to claim 1, characterized in that, The preparation method of polyacrylamide microspheres is as follows: S1. Acrylamide, crosslinking agent and photoinitiator are added to the solvent and magnetically stirred until completely dissolved to obtain a homogeneous aqueous precursor solution; then an oil phase system is prepared using an emulsifier. S2. Based on the above aqueous precursor solution and oil phase system, water-in-oil microspheres are formed by using a microfluidic chip, and then acrylamide in the aqueous material is polymerized by ultraviolet light to form PAAM microspheres. S3. After polymerization, the oil phase is discarded, and the PAAM microspheres are dispersed in deionized water. Unreacted impurities are removed by dialysis to obtain polyacrylamide microspheres with uniform size and neutral charge.
6. The preparation method according to claim 5, characterized in that, The mass ratio of acrylamide, crosslinking agent and photoinitiator in S1 is 2~5:0.01~0.038:0.01~0.
03.
7. The preparation method according to claim 5, characterized in that, The crosslinking agent used in S1 is N,N'-methylenebisacrylamide, the photoinitiator is α-ketoglutaric acid, and the emulsifiers are Span-20 and Span-80 in a mass ratio of 1:1~2.
8. A piezoelectric hydrogel that promotes myocardial repair, characterized in that, It is prepared by the method described in any one of claims 1 to 7.
9. Use of the piezoelectric hydrogel of claim 8 in the preparation of a medicament for promoting myocardial repair.
10. Use of the piezoelectric hydrogel of claim 8 in the preparation of a medicament for treating myocardial infarction.
